Gen Z’s Preferences in Choosing Villa in Kubu Village, Karangasem - Agung, Bangsawan Satria; Diwyarthi, Ni Desak Made Santi; Jata, I Wayan; Pinaria, Ni Wayan Chintya (Annusfy : Journal of Multidisciplinary Research, 2025)
This study aims to explore Generation Z’s preferences in choosing villa accommodations in Kubu Village, Karangasem. Generation Z is known for their closeness to technology and their desire for authentic experiences in every journey. This research employs a quantitative method with a survey approach involving respondents from Generation Z who have visited the area. The findings reveal that factors such as villa facilities, price, location, as well as the uniqueness and experiences offered, are the main considerations in accommodation selection. In addition, aspects of sustainability and alignment with personal values also play an important role in their decision-making process. Generation Z tends to choose accommodations that are not only comfortable and visually appealing but also provide added social and environmental value. This study provides valuable insights for villa owners and tourism managers in designing products that match the preferences and characteristics of Generation Z in Kubu Village, Karangasem.